( x - 7) ( x + 3 ) = 0
( 4x + 3 ) ( 2x + 1) = 0
Решите

алхожа алхожа    2   30.04.2020 10:13    0

Ответы
elyushik elyushik  14.10.2020 04:13

1. ( x - 7 ) ( x + 3 ) = 0

   x - 7 = 0

   x + 3 = 0

   x1= 7

   x2= - 3

( 7 - 7 ) ( -3 + 3 ) = 0

                       0 = 0

2. ( 4x + 3 ) ( 2x + 1) = 0

    4x + 3 = 0  

    2x + 1 = 0

     x1= 3/4 или 0,75

     x2= - 1/2 или - 0,5

( 4 * 3/4 + 3 ) ( 2 *  1/2 + 1) = 0

                                      0 = 0

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика